2013
DOI: 10.1158/1055-9965.epi-12-1238
|View full text |Cite
|
Sign up to set email alerts
|

Genes Associated with Prostate Cancer Are Differentially Expressed in African American and European American Men

Abstract: Background Despite more aggressive screening across all demographics and gradual declines in mortality related to prostate cancer (PCa) in the United States, disparities among populations persist. A substantial proportion of African American men (AAM) have a higher overall incidence, earlier age of onset, increased proportion of clinically advanced disease, and increased bone metastases and mortality from PCa compared to European American men (EAM). Limited early evidence indicates that underlying causes for d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 25 publications
8
129
1
1
Order By: Relevance
“…Several studies have highlighted molecular differences in PCa in AA and Caucasian men [22] including prevalence of transmembrane protease, serine 2/v-ets avian erythroblastosis virus E26 oncogene homolog (TMPRSS2-ERG) fusions [23] and phosphatase and tensin homolog (PTEN) deletions [24], and gene expression patterns [25]. Studies also suggest that increased androgen signaling is seen in AA men [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have highlighted molecular differences in PCa in AA and Caucasian men [22] including prevalence of transmembrane protease, serine 2/v-ets avian erythroblastosis virus E26 oncogene homolog (TMPRSS2-ERG) fusions [23] and phosphatase and tensin homolog (PTEN) deletions [24], and gene expression patterns [25]. Studies also suggest that increased androgen signaling is seen in AA men [26].…”
Section: Discussionmentioning
confidence: 99%
“…Genetics and the tumor microenvironment may explain a majority of racial disparities seen in prostate cancer. [25,26] Fine-mapping in men of African ancestry in the 8q24 region, which is known to harbor multiple prostate cancer susceptibility risk variants, has identified three new ancestry-specific risk variants. [27]…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings to the Glasgow studies are apparent in studies aiming to determine why men of African American (AA) race are two to three times more likely to die from prostate cancer that European Americans (EA) (Horner et al 2009). Gene expression microarray studies of prostate cancer tissues from AA and EA men have consistently shown overexpression of gene sets involving inflammation pathways in AA samples (Powell et al 2013;Reams et al 2009;Wallace et al 2008). This includes differentially expressed gene clustering in pathways involved in immune response, interleukins, and cytokine signaling and overexpression of specific genes such as IL-6, IL-8, and IL-1β (Powell et al 2013;Reams et al 2009;Wallace et al 2008).…”
Section: Additional Innate Immune Cells In Prostate Cancermentioning
confidence: 99%